The Influence of Social Media Use and Lifestyle on Purchase Decisions at Shopee (Study of Students at the Faculty of Social and Political Sciences, Riau University, Pekanbaru) - Mandataris; Soufyana Zahra Minda (Formosa Journal of Multidisciplinary Research, 2024)
This study, which involved students at the Faculty of Social and Political Sciences at Riau University in Pekanbaru, tries to ascertain the impact that social media users and lifestyle have on Shopee purchase decisions. Descriptive and quantitative statistics are used in this study, and multiple and simple linear regression analysis is the analytical technique. Purposive sampling procedures were employed to establish the sample size of 100 respondents for this study, and questionnaires were utilized to gather data. According to the research findings, social media use has a major positive impact on buying decisions, as does living a healthy lifestyle. At Shopee, social media and lifestyle have a major positive impact on purchasing decisions (Study on Students of the Faculty of Social Sciences and Sciences Politics Riau University Pekanbaru).